STRATEGI KOMUNIKASI DAKWAH BAZNAS KABUPATEN BARRU DALAM MENINGKATKAN KESADARAN BERZAKAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses the Da'wah Communication Strategy of the National Amil Zakat Agency (BAZNAS) in Barru Regency in increasing awareness of tithing, with the main problem of How the Barru Regency BAZNAS Da'wah Communication Strategy in Raising Awareness of Zakat and What are the Communication Barriers Faced by BAZNAS Barru Regency in Raising Public Awareness of The Importance of Zakat.This type of research is classified as qualitative research. The research approach used in da'wah communication. The subjects studied were the Deputy Chairperson of Baznas and Baznas staff. Data collection techniques were carried out by the methods of observation, interviews, and documentation. Techniques for processing and analyzing data by collecting data, reducing data, presenting data and drawing conclusions.The results of this study indicate that the Da'wah Communication Strategy of the National Amil Zakat Agency (BAZNAS) in Barru Regency in increasing awareness of zakat is carried out in several ways, namely forming a collecting unit (UPZ) in all components, umara commitments with ulama related to zakat management, strengthening ASN zakat and inviting new people who are successful outside the barru tithe at BAZNAS Barru. The communication barriers faced by Barru Regency in Raising Zakat Awareness are internal and external barriers. The internal barriers are the lack of extension workers and digital knowledge barriers, while the external obstacles are the people channeling zakat not through BAZNAS and the lack of public awareness of paying zakat, especially gold zakat.The implication of this research is that the BAZNAS of Barru Regency together with the new regional government needs to increase extension workers, especially gold zakat so that people can issue zakat on their gold assets and the zakat collection unit (UPZ) in all components must also be further improved. And for BAZNAS officers, they must better understand digital technology where information and communication technology is a very important part in interacting with the community, especially in the current covid-19 era.